Exploratory Study on the Load-Bearing Behaviour of Laminated Glass Beams Exposed to Fire - Maximilian Möckel; Katharina Lohr; Christian Louter (Challenging Glass Conference Proceedings, 2022)
All-glass structures have become increasingly popular with architects and builders in recent years. Glass surfaces are becoming larger and more impressive, while connections are being decreased to obtain maximum transparency. The supporting structure of glass facades, glass roofs or walk-on glazing is mostly made of metal. One of the reasons for this are the fire protection requirements. To increase the overall transparency load-bearing glass structures have recently been given more attention. However, their use is currently still limited due to the concerns about glass performance in case of fire. Within a research study at TU Dresden load-bearing tests in a furnace were carried out to examine the load-bearing behaviour of glass beams exposed to fire. Different glass types and interlayer materials were tested with varying loads. This study provides a closer look at fire performance of glass beams and proposes further examinations to increase the load-bearing capacity in case of fire.